Once - Gleitzman, Morris (London : Puffin Books, 2006)
After living in an Catholic orphanage for nearly four years, a naive Jewish boy runs away and embarks on a journey across Nazi-occupied Poland to find his parents.
Young Adult.
Young Adult
Keywords: Holocaust, Jewish (1939-1945) -- Poland -- Juvenile fiction; Jews -- Poland -- Juvenile fiction; Orphans -- Juvenile fiction; Separation (Psychology) -- Juvenile fiction; Survival -- Juvenile fiction; World War, 1939-1945 -- Poland -- Juvenile fiction; Historical fiction; Holocaust, Jewish (1939-1945) -- Poland -- Fiction; Jews -- Poland -- Fiction; Orphans -- Fiction; Separation (Psychology) -- Fiction; Survival -- Fiction; World War, 1939-1945 -- Poland -- Fiction; Historical fiction; Holocaust, 1933-1945 -- Poland -- Fiction; Jews -- Poland -- Fiction; Orphans -- Fiction; Separation (Psychology) -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; World War, 1939-1945 -- Poland -- Fiction; Poland -- History -- Occupation, 1939-1945 -- Juvenile fiction; Poland -- History -- Occupation, 1939-1945 -- Fiction; Poland -- History -- Fiction; Historical fiction